1958
DOI: 10.1111/j.1476-5381.1958.tb00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations Concerning the Action of 5‐hydroxytryptamine on the Peristaltic Reflex

Abstract: In isolated guinea-pig intestine 5-hydroxytryptamine increased the longitudinal muscle contractions in response to acetylcholine while the ganglionic action of nicotine was first facilitated and then blocked. Phenyldiguanide, veratrine, veratridine and protoveratrine, like 5-hydroxytryptamine, depressed the response to nicotine, leaving that to acetylcholine unaffected.The sensory stimulants, like 5-hydroxytryptamine, facilitated the peristaltic reflex when applied to the mucosa, and abolished it when applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
1

Year Published

1959
1959
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 20 publications
(9 reference statements)
6
78
1
Order By: Relevance
“…In a recent investigation Biilbring & Lin (1958) found that small amounts of 5-hydroxytryptamine (5-HT) were continuously released into the lumen of an isolated loop of ileum and that 5-HT, if applied intraluminally, stimulated peristalsis by its action on sensory receptors deeply seated in the intestinal mucosa. These findings have been extended by experiments on small intestine in situ (Bulbring & Crema, 1958, 1959a, but little is known about the effect of 5-HT on, and the release of 5-HT from, the large intestine. Moreover it is not known whether the release of 5-HT from the intestine is controlled by the extrinsic nerves.…”
mentioning
confidence: 97%
“…In a recent investigation Biilbring & Lin (1958) found that small amounts of 5-hydroxytryptamine (5-HT) were continuously released into the lumen of an isolated loop of ileum and that 5-HT, if applied intraluminally, stimulated peristalsis by its action on sensory receptors deeply seated in the intestinal mucosa. These findings have been extended by experiments on small intestine in situ (Bulbring & Crema, 1958, 1959a, but little is known about the effect of 5-HT on, and the release of 5-HT from, the large intestine. Moreover it is not known whether the release of 5-HT from the intestine is controlled by the extrinsic nerves.…”
mentioning
confidence: 97%
“…In part, this uncertainty arises because 5-HT has many actions on the neurons, muscle, and epitheHum of the gut and it has been difficult to determine which of these are of physiological significance. The neuronal effects of 5-HT include excitation of mucosal afferent fibers to initiate the peristaltic reflex (4,5), a presynaptic inhibition of the release of acetylcholine (AcCho) from activated myenteric axons (6), stimulation of excitatory enteric neurons to cause a net release of AcCho resulting in smooth muscle contraction, and a relaxation of the bowel secondary to the activation of nonadrenergic, noncholinergic inhibitory neurons (7). Direct application of 5-HT onto myenteric type II/AH neurons may result in a rapid depolarization of the cells associated with an increase in membrane conductance (8), a slow depolarization associated with a decreased membrane conductance (9,10), a hyperpolarization associated with an increase in membrane conductance, or, with different time courses, all of these responses (11)(12)(13).…”
mentioning
confidence: 99%
“…Additionally, in some species, including mice, mast cells contain 5-HT (4). It is well established that endogenous 5-HT released from mucosal EC cells activates intrinsic primary afferent neurons to initiate the peristaltic reflex in the small intestine (6,14). A similar pathway is proposed in the stomach: food stimulates mucosal EC cells, which in turn activate primary afferent neurons initiating gastric accommodation via the vagovagal reflex pathway.…”
mentioning
confidence: 99%